Поняття публічного порядку як об’єкта адміністративно-правового регулювання - Герасимчук, Р. В.; Herasymchuk, R. V. (Вісник Харківського національного університету внутрішніх справ. – 2022. – № 3 (98). – С. 115-120, 2022)
Акцентовано увагу на відсутності єдиного теоретичного підходу до визначення поняття «публічний порядок», зокрема як об’єкта адміністративно-правового регулювання. Розкрито наукові думки вчених щодо тлумачення цієї наукової категорії. Визначено, що поняття публічного порядку прийшло на заміну громадському не тільки завдяки розвитку законодавства, але й завдяки посиленню компаративістських досліджень. Запропоновано авторське розуміння поняття публічного порядку як об’єкта адміністративно-правового регулювання.

Based on a comprehensive study of the researches’ scientific views, the concept of public order as an object of administrative and legal regulation has been investigated and its author’s definition has been proposed. An in-depth analysis of scientific literature has shown that the concept of public order has replaced the public not only due to the development of legislation, but also due to the strengthening of comparative studies. It is emphasized that the absence of public order, that is, the situation when everyone does what they want and can violate the rights of others, while committing socially dangerous acts, makes it impossible to feel the protection of the state’ opulation. It is stated that public order is: a) a qualitative characteristic of social relations in the field of public security, which provides for the use by each person of his or her rights and freedoms to the extent determined by society and regulated by the norms of current legislation; b) a system of special imperative requirements for each representative of society and his or her behaviour, which are ensured by state measures, in particular coercive ones, and which cannot violate the norms of public morality, social interests, individual human rights and/or carry social danger; c) a system of social and economic rights and freedoms, which are regulated by the norms of current legislation. According to the results of the study, it has been determined that public order as an object of administrative and legal regulation is a public legal relationship regulated by the norms of current administrative legislation, which arise in relation to the creation of such a social order in which the legitimate rights, interests and freedoms of man and citizen cannot be violated by other persons, public authorities and local self-government bodies.

Акцентировано внимание на отсутствии единого теоретического подхода к определению понятия «публичный порядок», в частности, как объекта административно-правового регулирования. Раскрыты научные мнения ученых о толковании этой научной категории. Определено, что понятие публичного порядка пришло на замену общественному не только благодаря развитию законодательства, но и усилению компаративистских исследований. Предложено авторское понимание понятия публичного порядка как объекта административно-правового регулирования.
The concept of public order as an object of administrative and legal regulation
Герасимчук, Р. В. Поняття публічного порядку як об’єкта адміністративно-правового регулювання / Руслан Володимирович Герасимчук // Вісник Харківського національного університету внутрішніх справ. – 2022. – № 3 (98). – С. 115-120. - DOI: https://doi.org/10.32631/v.2022.3.10.
Keywords: Адміністративне право та процес. Administrative Law and Procedure. Административное право и процесс; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; публічний порядок; public order; публичный порядок; адміністративно-правове регулювання; administrative and legal regulation; административно-правовое регулирование; порядок; order; погляди вчених; views of scientists; взгляды ученых